2013
DOI: 10.1182/asheducation-2013.1.184
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of tyrosine kinase inhibitors in chronic myeloid leukemia: when is this a safe option to consider?

Abstract: Mrs G is a 54-year-old woman with a diagnosis of chronic-phase chronic myeloid leukemia dating back 8 years. She had a low-risk Sokal score at diagnosis and was started on imatinib mesylate at 400 mg orally daily within one month of her diagnosis. Her 3-month evaluation revealed a molecular response measured by quantitative RT-PCR of 1.2% by the International Scale. Within 6 months of therapy, she achieved a complete cytogenetic response, and by 18 months, her BCR-ABL1 transcript levels were undetectable using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Although treatment-free remission is currently only possible for highly selected patients within clinical trial confines, in the future this may become the treatment goal for patients with good-risk disease. 2 However, some patients still progress to accelerated phase or blast crisis. A strategy to promptly identify patients truly requiring additional therapy is among the top priorities for CML research.…”
Section: Discussionmentioning
confidence: 99%
“…Although treatment-free remission is currently only possible for highly selected patients within clinical trial confines, in the future this may become the treatment goal for patients with good-risk disease. 2 However, some patients still progress to accelerated phase or blast crisis. A strategy to promptly identify patients truly requiring additional therapy is among the top priorities for CML research.…”
Section: Discussionmentioning
confidence: 99%
“…According to ELN guidelines BCR-ABL transcript level >10% entitles us to change of imatinib therapy on TKI second generation [8]. Future directions for us will focus on the possibility of discontinuation of TKI therapy and potential cure of CML [9].…”
Section: Targeted Therapy In Chronic Myeloid Leukemiamentioning
confidence: 99%
“…43 In a recent evidence-based mini review presented at the American Society of Hematology meeting in 2013, seven prospective and two retrospective trials were analyzed; it was concluded that selected patients, perhaps half of them, may remain treatment-free for a long period of time. 44 The information in relation to dasatinib and noilotinib discontinuation in CML-CP is limited, 45 but since these drugs are more potent than imatinib and capable of producing higher CMR rates, it is reasonable to expect similar or better long-term results after discontinuation of these second-generation TKI. We can assume that cure is possible in a subset of CML patients, but further identification of this subgroup is necessary.…”
Section: Tki Treatment Expectationsmentioning
confidence: 99%